THE INVESTIGATION OF MAJOR PREDICTORS OF WELL-BEING IN A SAMPLE OF ROMANIAN UNIVERSITY STUDENTS IN THE POST-COVID-19 PERIOD - Éva KÁLLAY (Studia Universitatis Babes-Bolyai, 2022)
The Coronavirus-induced pandemic has had a significant impact on the physical and psychological functioning of the entire world's population. Research has indicated that besides the physical threat to health itself, the implications of constant uncertainty, separation from and/or loss of loved ones, loss of freedom to travel, shortage of food and financial resources, disruptions of usual life-routines, changing work and learning habits, further aggravate the effect of initial stressors, leading to increased levels of depressive symptoms, anxiety, PTSD, insomnia, lowered levels of well-being, and confusion. Unfortunately, just as the two-years long pandemic ended, the Ukrainian war started, and the Romanian population, since our country borders Ukraine, has experienced a novel type of stress, that of the possibility of being attacked, affected economically. Almost simultaneously, the online education has returned to classical form of teaching, amidst semester, being another stress factor for students. Our results indicated that the two-year long pandemic was considered as having the greatest impact by almost two-thirds of the students. Furthermore, the lack of self-efficacy component of perceived stress was a constant and strong predictor of all components of well-being (subjective and psychological), and perceived helplessness for subjective well-being. Regarding emotion regulation strategies refocus on planning, positive reevaluation, self- and other blame, withdrawal and actively approaching the source of stress proved to be the most important predictors. The results of our investigation may be beneficial for the tailoring of future prevention and intervention programs that would target the enhancement of psychological adaptation of students.